Proceedings of the 1997 Academy of Marketing Science (AMS) Annual Conference - Wilson, Elizabeth J.; Hair, Jr., Joseph F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume includes the full proceedings from the 1997 Academy of Marketing Science (AMS) Annual Conference held in Coral Gables, Florida. The research and presentations offered in this volume cover many aspects of marketing science including marketing strategy, consumer behaviour, global marketing, advertising, branding, marketing education, among others. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy$1 (Bs flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.s
Poster Session -- Destination Branding -- Measuring Consumer Responses to Marketplace Stimuli -- Innovation in Marketing Instruction -- Ethical Issues in Marketing -- Developing Measurement Tools for Global Marketing -- Supplier Satisfaction or Satisficing? -- Using the Internet and World Wide Web in the Marketing Classroom -- Customer Satisfaction Research Topics -- Relationship Marketing and Strategic Alliances -- Creating Ethical Compliance Systems in Marketing Organizations -- Strategic Issues in Global Marketing -- The Role of Value in Marketing Management -- Salesforce Performance -- The Marketer as Entrepreneur -- Ethics and the Marketing Educator -- Advertising at the Crossroads: The Emerging Challenges -- Retail Channel Climates: The Heat is On -- Continuing Controversies on Ethical Issues in Global Marketing Management -- Branding, Country of Origin, and Control Issues in Global Marketing -- Issues in Sales Management -- Developing and Managing Products -- Antecedents and Consequences of Marketing Strategies -- Cross-Functional Issues in the Market-Oriented Firm -- Issues in Global Marketing Management -- Sales Management -- Strategic Marketing for the 21st Century -- The Internet and Marketing Pedagogy -- Strategic and Managerial Issues in Services Marketing -- Current Issues in Research Methodology -- Information Technology and the Future of Marketing Communications -- Issues in Technology and the Internet -- Consumer Behavior in a Services Context: Quality, Satisfaction, Switching -- Global Distribution and Logistics -- Nonpersonal Communication Strategies.
Keywords: Economics; Marketing; Economics/Management Science; Marketing; Business Strategy/Leadership.; Sales/Distribution/Call Center/Customer Service